Enigmatic traces determined on radical perineal prostatectomy specimens: An anatomohistological study - Akça, Oktay; Yalçın, Savaş; Horuz, Rahim; Boz, Mustafa; Kafkaslı, Alper; Çetinel, Cihangir; Göktaş, Cemal; Çakır, Çağlar; Albayrak, Selami (Journal of Clinical and Analytical Medicine, 2014)
Aim: An anatomohistological evaluation of tissue found on specimens of radical perineal prostatectomy which could influence oncological and functional outcome. Material and Method: A certain surgeon's batch of 41 RPP (Radical perineal prostatectomy) specimens were evaluated. The RPP specimens were dissected from apex to basis. The following slices were dissected: 1 from the Apex, 2 from the center of the prostate, and 1 from the basis. Totaling 4 selected slices. Tissue surrounding these slices were anatomohistologically evaluated working from the following 7 parameters determined in light of latest anatomical and pathological insight on the prostate:"Dorsal venous complex(DVC)", "Striated muscle(Rhabdosphincter)", "Periprostatic fascial tissue (PPFT)", "Neurovascular bundle(NVB)", "Bladder neck smooth muscle", "Surgical margins" and "Capsular incision". Results: Whilst no DVC was found in the dissected Apex slices, muscle striation was found with 39 (95,1%) of the patients. PPFT within central prostate sections was found with 36 (87,8%) of the patients, predominantly within posterior quadrants. Again within central prostate sections NVB was found with 23 (56%) of the patients. All basis slices were found to have bladder neck smooth muscle. Surgical margin positivity was found with only 5 (12,1%) of the patients. Capsular incision was found with 15 (36,5%) of the patients. Discussion: Our study provides a quantitative report of the extent to which other anatomi-cal structures are extracted when removing the prostate from the perineum employing the RPP technique. That the specimen show no trace of DVC is significant in terms of pubovesical complex sparing.

Amaç: Radikal perineal prostatektomi spesmenleri (RPP) üzerinde bulunan, onkolojik ve fonksiyonel sonuçları etkileyebilecek dokuların anatomohistolo-jik değerlendirmesi. Gereç ve Yöntem: Tek cerrahın serisi olan 41 RPP spes-meni incelendi. Spesmenler apeksten basise doğru dilimlendi. Apeksten 1, orta prostattan 2 ve basisden 1 adet olmak üzere toplam 4 adet dilim seçildi. Bu dilimleri çevreleyen dokular, prostatın güncel anatomik ve patolojik veri-leri ışığında belirlenmiş 7 parametre açısından anatomohistolojik olarak de-ğerlendirildiler; “Dorsal venöz kompleks”, “Çizgili kas (rabdosfinkter)”, “Perip-rostatik fasiyal doku”, “Damar sinir paketi”, “Düz kas (mesane boynu)”, “Cer-rahi sınır” ve “Kapsüler insizyon”. Bulgular: Apeksten alınan dilimlerde dorsal venöz kompleks hiç gözlenmezken 39 (%95,1) hastada çizgili kas vardı. Orta prostattan alınan dilimlerde periprostatik fasiyal doku, özellikle rektum tara-fında bulunan posterior kesitlerde olmak üzere, 36 (%87,8) hastada gözlendi. Yine orta prostatta damar sinir paketi 23 (%56) hastada gözlendi. Tüm basis dilimlerinde mesane boynuna ait düz kas lifleri vardı. Cerrahi sınır pozitifliği sadece 5 (%12,1) hastada vardı. Kapsüler insizyon 15 (%36,5) hastada göz-lendi. Tartışma: Çalışmamız, RPP tekniği uygulanırken prostatla birlikte baş-ka hangi dokuların çıktığını kantitatif olarak ortaya koymuştur. Spesmenlerin dorsal venöz kompleksi içermiyor olması pubovesikal kompleksin korunuyor olması açısından anlamlıdır.
Radikal perineal prostatektomi spesmenlerindeki gizemli izler: Bir anatomohistolojik çalışma
Keywords: Facia; Perineal; Prostatectomy